Genes Associated with Fibro-Osseous Lesion: A Review Article - Tariq Soyab (Institute of Medico-legal Publications Pvt Ltd, 2020)
The Fibro osseous lesion is a group of diseases or lesions that are affecting the skeletal tissue which frequentlyincludes maxilla and mandible. The disease can also be easily described as bone disorders. A lot of researchand work has been done regarding this serious disease though due to similarities in its radiographical featuresor histopathology, it is been very complicating to diagnose and classify FOLs. The review article focuses ondifferent diseases that come under the fibro-osseous lesion and the genes which have been associated withthe respective one in an orderly manner with their Histopathological features. One to understand this lesionthe clinical correlation with radiographic involvement is necessary to diagnose this kind of dysplasia. Thearticle also throws light on that the mandible and maxilla also suffer from localized and generalized formsof skeletal dysplasia which results in disproportionate short stature. These dysplasias always remain in aconfused manner for their nomenclature. Much classification has been proposed by the different authors indifferent years regarding the FOLs based on gene or protein defect in these disorders.